10.1093/gao/9781884446054.013.7002292402 (Inactive DOIs, 2018)
Health and biomedical science-related academic societies have played significant roles in the development and evolution of science and medicine, as well as the evolution of disciplines, including the diversification of medicine into specialties and subspecialties. They have also had formative roles in the development of clinical practice, professionalism, and training standards. The communities they establish promote knowledge creation and dissemination, provide career and professional development opportunities, articulate professional matters, offer networking opportunities, provide recognition, support members, and perform public engagement and advocacy work. They also play increasingly important roles in educating the public and disseminating objective, evidence-based medical and scientific information. Academic societies face challenges related to membership (recruiting new members and engaging and retaining current members), technology, hosting meetings and conferences, generational shifts (e.g., in demographics and attitudes toward working conditions, career paths, work-life integration), costs and logistics related to operations, and morale within institutions and professions. The Council of Faculty and Academic Societies of the Association of American Medical Colleges plays a unique role in supporting academic medical and related societies by providing an interprofessional forum for their interaction and dialogue, and is a vehicle for asserting their collective voice. To the extent that past is prologue, future advances in health care and science will depend, in part, on the resilience of academic societies and on the health professional workforces that they nourish.